DEFRAGMENTATION THINKING STRUCTURE TO OVERCOME ERRORS IN ADDRESSING MATHEMATICAL PROBLEM - Andriani, Siti Puri; Triyanto, Triyanto; Nurhasanah, Farida (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This research is intended to describe students' procedural errors in solving problems derivative of algebraic functions and efforts to overcome these errors by using the defragmentation process. Error analysis is carried out based on the procedural error theory based on Elbrink which includes the following aspects of errors: 1) Mis-identification; 2) Mis-generalization; 3) Repair Theory; and 4) Overspecialization. The subjects in this study are students of class XII MIPA Islamic State Senior High School (MAN) 3 Tulungagung taken from snowball random sampling. In taking the subject, the researchers select one of the students who make procedural errors by considering the completeness of the students when solving the given problems based on the problem-solving phase according to Polya. Based on the results of this study, it is found that the procedural errors made by the students are repair theory errors and overspecialization. The defragmenting process to correct these errors is intended to provide dis-equilibration and scaffolding. The results after the defragmenting process are the students can correct their mistakes and the structure of their thinking.Keywords: Defragmenting structure thinking; derivative algebraic functions; problem solving; procedural errors. AbstrakPenelitian ini bertujuan untuk menggambarkan kesalahan prosedural siswa dalam menyelesaikan masalah turunan fungsi aljabar dan upaya untuk mengatasi kesalahan tersebut dengan menggunakan proses defragmenting. Analisis kesalahan dilakukan berdasarkan konsep teori kesalahan prosedural menurut Elbrink yang mencakup aspek kesalahan sebagai berikut: Mis-identificstion; 2) Mis-generalization; 3) Repair Theory; dan 4) Overspecialization. Subjek dalam penelitian ini adalah siswa kelas XII MIPA MAN 3 Tulungagung yang diambil secara snowball random sampling. Dalam pengambilan subjek dipilih salah satu siswa yang melakukan kesalahan prosedural dengan mempertimbangkan kelengkapan siswa ketika menyelesaikan masalah yang diberikan berdasarkan tahap pemecahan masalah menurut Polya. Dari hasil penelitian ini ditemukan bahwa kesalahan prosedural yang dilakukan siswa ialah kesalahan repair theory dan overspecialization. Proses defragmenting yang dilakukan untuk memperbaiki kesalahan tersebut ialah dengan memberikan dissequillibrasi dan scaffolding. Hasil yang diperoleh setelah proses defragmenting dilakukan ialah siswa mampu memperbaiki kesalahannya dan struktur berpikirnya.Kata kunci: Defragmenting struktur berpikir, kesalahan prosedural, pemecahan masalah, turunan fungsi aljabar.